Exploring illusion in the work of Robin Rhode and Lauren Moffatt through the investigation of truth, reality, and perception - Van Rooyen, Magdel (University of Pretoria, 2023)
Dissertation (MA (Visual Arts))--University of Pretoria, 2022.